THE APPLICATION OF ART THERAPY TO REDUCE THE LEVEL OF DEPRESSION IN PATIENTS WITH HEMODIALYSIS - Atikah Fatmawati; M. Rachmat Soelaeman; Imas Rafiyah (Belitung Raya Foundation, Indonesia, 2018)
Background: Depression can occur in patients with chronic kidney disease undergoing hemodialysis and can lead to decreased quality of life, and will have a two-fold risk for the occurrence of death and hospitalization. Objective: The purpose of this study was to identify the effects of art therapy on the level of depression patients with hemodialysis. Methods: This study used a quasi-experimental method with pretest posttest with control group design. Collecting data using questionnaires of Beck Depression Inventory (BDI-II) versions of Indonesia, which was done twice, before and after art therapy intervention. Data were analyzed using paired t-test and unpaired t-test. Results: The results showed that after given intervention of art therapy there were differences in the average scores of depression in the intervention group (t = 0.764; p-value = 0.000). Art therapy is a medium to expose and express the feelings, fears or perceived problem, so it can be used as an adaptive coping method in patients with chronic kidney disease undergoing hemodialysis. Conclusion: It is concluded that art therapy could reduce depression in patients with chronic kidney disease undergoing hemodialysis. Nurses can act as a facilitator to provide art-based therapy in order to improve the ability of psychological adaptation in patients with chronic kidney disease undergoing hemodialysis.